Transformasi Pengelolaan Pembelajaran Berbasis Kurikulum Merdeka - Kurnia Puspita; Putri Kartiwi, Asti (UNIVERSITAS BENGKULU, 2023)
Change in the world is very fast. Specifically in the world of education, changes often occur due to thedemands of curriculum changes that are tailored to the learning needs of today's students. The purpose of this researchis to describe the transformation of planning, organizing, implementing, and evaluating learning as well as problemsand solutions in the transformation of learning management in the independent curriculum at SD Negeri 16 SouthBengkulu. The research approach used is descriptive-qualitative. The subjects in this study were the principal, viceprincipal, and teachers. The data collection techniques used are interviews, observation, and documentation. Theanalysis technique uses data reduction, conclusion drawing, summarizing research results, and data triangulation. Theresults showed that since 2 years, SD Negeri 16 Bengkulu Selatan has implemented an independent curriculum,starting with changes in planning, organization, implementation, and evaluation of learning in stages with the supportof all school stakeholders and the surrounding community. The problems that arise are related to the technology thatmust be used in implementing the independent curriculum, but the school's solution is to provide continuousassistance from the driving school facilitator and supervisor to motivate teachers to use the independent teachingplatform. Advice is given to the school to continue to carry out learning reflection activities once every 3 months tofind out the problems that arise internally and find solutions together. Collaboration in the implementation of